The Influence of Competence, Work Discipline, and Organizational Climate on Employee Performance at the Kayon Resort Ubud, Gianyar - Anak Agung Istri Cinta Dewi; Ni Putu Irmayanti; Ni Made Widiari Rahayu; Ni Ketut Istha Lestari; Ni Kadek Sinta Oktaviana Prana Dewi; Nengah Landra; Gde Bayu Surya Parwita (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Employee performance is one of the key indicators in assessing the quality of human resources within an organization or company. To improve performance, companies generally implement various strategies, such as training programs, educational development, enforcement of work discipline, motivational efforts, and the management of a supportive work environment. This study aims to analyze the influence of competence, work discipline, and organizational climate on employee performance at The Kayon Resort Ubud. This research involved all employees of The Kayon Resort Ubud as the population. The sampling technique used was a saturated sampling method, in which the entire population was included as the research sample, totaling 71 respondents. To analyze the relationships between variables and test the hypotheses, multiple linear regression analysis was employed. The results of the study indicate that competence has a positive and significant effect on employee performance. Likewise, work discipline and organizational climate also have a positive and significant influence on employee performance at The Kayon Resort Ubud. Based on these findings, future researchers are encouraged to expand the study by including other variables that may affect employee performance.